2020
DOI: 10.1029/2020wr027112
|View full text |Cite
|
Sign up to set email alerts
|

Nonstationary Frequency Analysis of Censored Data: A Case Study of the Floods in the Yangtze River From 1470 to 2017

Abstract: Censored data (CD) of floods, that is, the combination of systematic data (SD) and historical data, can help improve the robustness of flood frequency analysis, due to its temporal information expansion. However, in nonstationary flood frequency analysis, the approach to utilize the CD has rarely been investigated. In this study, a covariate‐based nonstationary flood frequency analysis framework based on various likelihood functions using the generalized extreme value (GEV) distribution was built to utilize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 62 publications
(100 reference statements)
1
23
0
Order By: Relevance
“…The rest reduction induced by the reservoirs above Wulong is 2,045 m 3 /s, making a relative contribution of 14% to the total reduction. This finding generally agrees with the previous studies, in which the TGR was also found to have the largest contribution in declining the flood magnitude of the whole Upper Yangtze basin (Jiang, Zhang, & Luo, 2019; B. Xiong et al., 2020).…”
Section: Results and Analysissupporting
confidence: 93%
See 2 more Smart Citations
“…The rest reduction induced by the reservoirs above Wulong is 2,045 m 3 /s, making a relative contribution of 14% to the total reduction. This finding generally agrees with the previous studies, in which the TGR was also found to have the largest contribution in declining the flood magnitude of the whole Upper Yangtze basin (Jiang, Zhang, & Luo, 2019; B. Xiong et al., 2020).…”
Section: Results and Analysissupporting
confidence: 93%
“…10.1029/2020WR029374 13 of 21 found to have the largest contribution in declining the flood magnitude of the whole Upper Yangtze basin (Jiang, Zhang, & Luo, 2019;B. Xiong et al, 2020).…”
Section: Attribution Of Flood Decline In the Upper Yangtze Basinmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonstationary FFA (NFFA) is proposed to address the nonstationary (NS) issue of extreme flood events. As evidenced from recent review articles, there are several different methods for NFFA (Khaliq et al 2006;Hall et al 2013;Madsen et al 2014;Bayazit 2015;Hao & Singh 2016;Yan et al 2017b;Salas et al 2018;Jiang et al 2019;Qu et al 2020;Xiong et al 2020;Yan et al 2021), among which the time-varying moments (TVM) method is the most popular approach. In the TVM method, the statistical parameters of flood distribution are no longer invariant but change with time or other covariates to capture the trend of flood frequency (Rigby & Stasinopoulos 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Impacts of climate change and anthropogenic activities on streamflow regime have drawn considerable attention recently [18][19][20][21][22][23]. A vast literature has thus been devoted to exploring non-stationarity in streamflow series worldwide [24][25][26][27][28][29][30][31]. However, most studies focus on extreme streamflow such as flood or low flow, while few studies have investigated them simultaneously.…”
Section: Introductionmentioning
confidence: 99%